'TAWHID' (MONOTHEISM) TRILOGY EXISTED IN TEACHING MATERIALS OF AKIDAH AKHLAQ IN THE 2013-CURRICULUM - Muhammad Mansur (Tadibia Islamika, 2021)
This research reveals the idea of the tauhid trilogy theory which roots from Salafis and its existence in the latest 2013 curriculum teaching modules of Akidah Akhlaq from several publishers in various cities which become a reference for teachers and writers for students at the high school level are equivalent, of course from the teaching process from the teacher, from the point of view of education, it will have a real impact, both the impact of theological thinking to character and real attitude in the form of real action. In this study the authors used a qualitative approach, an approach that emphasizes the analysis on the deductive and inductive inference processes as well as on the analysis of the dynamics of the relationship between observed phenomena. From this research, we obtain descriptive data describing the objectives and material, training and evaluation that learning the tauhid trilogy has a tremendous impact on students' beliefs and even becomes the attitude of real action. The data obtained through observation and documentation are then processed into information. The big conclusion from this research will strengthen the views of the moderate Ahlussunnah wal Jama’ah on the tauhid trilogy who have theological problems. This view is strengthened by tracing the genealogy of its roots of thought and the basics of its foundation from the holy texts of Quran and hadits, then discussing it scientifically and concluding it carefully so it can be justified with the considerations of experts from both competent theologians, commentators and legal practitioners. Based on that, this research shows that generally the thought of this tauhid trilogy is a new thing in the realm of Islam, especially in terms of the reasoning of faith which did not exist during the Shalaf Shaleh generation, whose validity is also still debatable, problematic and questionable. In particular, if we investigate further from the development of education, it will have a big impact on society, not only peace in religion, but it can shake religious moderation and lead to anti-tolerant attitudes but to acts of anarchism, radicalism and terrorism that justify the blood flow of fellow believers and same religion, country, and nation.